Analisis Dampak Pendampingan Dan Pelatihan Model Penilaian Melalui Media Online Terhadap Kompetensi Guru Pendidikan Agama Buddha - Hesti Sadtyadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This study aims to conduct a survey based on the results of mentoring and training in the preparation of assessment models for teachers of Buddhist education, and to analyze the level of success of teachers in the application of learning with online media, as well as the correlation of mentoring and teacher competence in the field of evaluation of Buddhist education. This research is a survey research, which is accompanied by experiments through training, in identifying and developing an assessment model using online media. As the results of the study show that the assistance of making an assessment model can enhance the teacher's role in producing valid assessments. The benefits from the implementation of mentoring and training result in a good assessment. This activity has a positive correlation between the mentoring process and increasing teacher competence in the field of assessment of Buddhist religious education. The magnitude of the correlation between material and competence has a high correlation, presentation and competence have a high enough correlation, and both have a significant positive relationship. Keywords : assessment model; online media; teacher competence